Lightweight high-toughness high-frequency wave-transparent composite material and preparation method thereof
By adding borosilicate hollow glass microspheres and low-polar toughening agent to the epoxy resin and molding, the problems of high high-frequency dielectric loss and insufficient material flatness in the prior art are solved, and the low dielectric loss and high bending toughness of composite materials are achieved, which is suitable for electronic products in the 5G communication era.
Patent Information
- Application Number
- CN202411693331.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
The existing epoxy resin composite materials have large dielectric constant and dielectric loss at high frequencies, which affects the transmission of 5G high-frequency signals, and the material flatness and utilization rate are insufficient after molding.
By adding borosilicate hollow glass microspheres and low polarity toughening agent to the epoxy resin, mixing resin glue, immersing the glass fiber cloth and molding it, a composite material with low dielectric loss and high bending toughness was prepared.
The dielectric loss of composite materials is achieved at 5GHz below 0.01, which improves the high-frequency signal transmittance and bending toughness of the material, which is suitable for the needs of consumer electronic product shells and peripheral products in the 5G communication era.
Smart Images

Figure CN119502410A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and more specifically, to a light-weight, high-toughness, high-frequency, wave-transmitting composite material and a preparation method thereof. Background Art
[0002] As consumers pursue thinner and lighter consumer electronic products such as mobile phones and tablets, glass fiber cloth reinforced epoxy resin composite materials are increasingly widely used in the shells and surroundings of consumer electronic products. Due to the personalized needs of consumer electronic products, the shells of mobile phones, tablets and other consumer electronic products are designed into 2.5D or 3D structures, which usually need to be prepared by compression molding.
[0003] A Chinese patent document with publication number CN114801244A discloses a processing technology for a lightweight 3D back cover for a mobile phone, wherein a lightweight 3D back cover is prepared by using electronic glass fiber cloth, a resin glue containing hollow glass microbeads and a panel layer.
[0004] The above technical solution has defects: the dielectric constant and dielectric loss of the epoxy resin used at high frequencies are relatively large, which is not conducive to the penetration of 5G high-frequency signals; in addition, by laying the epoxy glass fiber layer at 45° to ensure the bending toughness of the mobile phone shell after molding, the utilization rate of the raw materials is reduced and the flatness of the shell material after molding is affected, which is not conducive to subsequent assembly. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a lightweight, high-toughness, high-frequency wave-transparent composite material and a preparation method thereof, which has the advantages of low dielectric loss, high toughness and suitability for compression molding.
[0006] The above technical objectives of the present invention are achieved through the following technical solutions: a method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material, comprising the following steps:
[0007] S1. Add modified epoxy resin, low polar toughening agent, low polar curing agent and accelerator to the solvent, stir to dissolve evenly, then add borosilicate hollow glass microspheres, stir to disperse evenly, and obtain resin glue;
[0008] S2, immersing the glass fiber cloth into the resin glue solution, taking it out after it is completely soaked, and baking it to obtain a prepreg;
[0009] S3, stacking a plurality of the prepregs, placing them in a mold, and heating them at 120-200°C and 5-25kg / cm 2 The mold is pressed for 5-30 minutes under the conditions of , and then demoulding and placing in a shaping fixture for cooling to obtain the target product;
[0010] The low polar toughening agent includes one or more of epoxidized polybutadiene, maleic anhydride modified butadiene-styrene copolymer and terminal hydroxyl polybutadiene, and the density of the borosilicate hollow glass microspheres is 0.2-0.6 g / cm 3 , particle size D50 is 30-75μm, and particle size D90 is 60-120μm.
[0011] In one embodiment, the low polarity curing agent includes one or more of active ester, styrene maleic anhydride resin, benzoxazine resin and bismaleimide resin.
[0012] In one embodiment, the mass fractions of each component in the resin glue are:
[0013] 80-120 parts of modified epoxy resin;
[0014] 5-50 parts of low polar toughening agent;
[0015] 20-100 parts of low polarity curing agent;
[0016] Accelerator 0.5-1.5 parts;
[0017] 20-80 parts of borosilicate hollow glass microspheres.
[0018] In one embodiment, the modified epoxy resin includes one or more of dicyclopentadiene phenol modified epoxy resin, biphenyl type epoxy resin and isocyanate modified epoxy resin.
[0019] In one embodiment, the accelerator includes one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, N,N-dimethylaminopyridine, 2,4,6-tris(dimethylaminomethyl)phenol and diisopropylbenzene peroxide.
[0020] In one embodiment, the solvent includes one or more of acetone, butanone, xylene, ethylene glycol monomethyl ether and cyclohexanone.
[0021] In one of the embodiments, the method for preparing a lightweight, high-toughness, high-frequency, wave-transparent composite material according to claim 1 is characterized in that: said S1 also includes adding an auxiliary agent, and the auxiliary agent includes one or more of a pigment, a cross-linking auxiliary agent, an antioxidant and a UV absorber.
[0022] In one embodiment, the baking temperature in S2 is 100-180° C., and the baking time is 2-10 min.
[0023] In one embodiment, the glass fiber cloth is electronic grade glass fiber cloth, and the basis weight of the electronic grade glass fiber cloth is 48-105g / m 2 .
[0024] A light-weight, high-toughness, high-frequency, wave-transmitting composite material is prepared by the preparation method of the light-weight, high-toughness, high-frequency, wave-transmitting composite material.
[0025] The above-mentioned lightweight, high-toughness, high-frequency, wave-transmitting composite material and its preparation method have the following beneficial effects:
[0026] The present invention adds borosilicate hollow glass microspheres to a specially formulated epoxy resin composition with lower polarity, so that the prepared composite material has the characteristics of low density, low dielectric, high strength and low dielectric loss. The dielectric loss at 5GHz can be lower than 0.01, so it has higher high-frequency signal transmittance. In addition, by adding a low-polarity toughening agent, the bending toughness of the composite material is improved without affecting the flatness, which is more suitable for the demand for consumer electronic product casings and peripheral products in the 5G communication era. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a flow chart of the steps of the present invention;
[0028] Figure 2 The figure is a comparison diagram of the reaction mechanism of curing epoxy resin with different curing agents in the present invention. DETAILED DESCRIPTION
[0029] The present invention is described in further detail below in conjunction with the embodiments. It should be noted that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on it. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definitions in this specification shall prevail.
[0030] As used herein, the term "prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0031] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0032] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.
[0033] A method for preparing a light, high-toughness, high-frequency, wave-transmitting composite material, such as Figure 1 As shown, the following steps are included:
[0034] S1. Add modified epoxy resin, low polar toughening agent, low polar curing agent and accelerator to the solvent, stir to dissolve evenly, then add borosilicate hollow glass microspheres, stir to disperse evenly, and obtain resin glue;
[0035] This step is the preparation of the resin glue. In practical applications, one or more modified epoxy resins, low-polarity toughening agents, low-polarity curing agents and accelerators are initially added to the solvent to dissolve to form a homogeneous solution, and then the borosilicate hollow glass microspheres are gradually added in batches and stirred at a medium speed to be evenly dispersed.
[0036] S2, immersing the glass fiber cloth into the resin glue solution, taking it out after it is completely soaked, and baking it to obtain a semi-cured sheet;
[0037] The process parameters of gluing are determined by the gel time of the resin glue, the physical properties of the semi-cured sheet to be prepared, the gluing equipment used, etc. The main physical properties of the semi-cured sheet include resin content and resin fluidity. In practical applications, the resin content of the semi-cured sheet is higher than 40%, and the resin fluidity is greater than or equal to 15%.
[0038] S3, stack multiple prepregs, place them in a mold, and heat at 120-200℃, 5-25kg / cm 2 The mold is pressed for 5-30 minutes under the conditions of , and then demoulding and placing in a shaping fixture for cooling to obtain the target product;
[0039] In actual production, the number and specifications of the stacking of semi-cured sheets can be flexibly designed according to actual needs. Semi-cured sheets with the same formula and physical properties can be stacked, or multiple semi-cured sheets of different specifications can be stacked and combined in a certain order to obtain a stacked composite layer; the stacked composite layer is then placed in a mold covered with a release film or coated with a release agent, and molded according to the set temperature and pressure; after the molding is completed, the completely molded sheet is taken out of the mold, placed in a molding fixture and cooled to room temperature to obtain a lightweight, high-toughness, high-frequency, wave-transparent composite material with a 3D structure.
[0040] The low polar toughening agent includes one or more of epoxidized polybutadiene, maleic anhydride modified butadiene-styrene copolymer and terminal hydroxyl polybutadiene, and the density of the borosilicate hollow glass microspheres is 0.2-0.6 g / cm 3 , particle size D50 is 30-75μm, and particle size D90 is 60-120μm.
[0041] A low polar toughening agent is used to reduce the polarity of the resin glue and improve the toughness of the glue. In addition, the hydroxy-terminated polybutadiene has a low dielectric constant and loss, which can significantly improve the dielectric properties of the target product.
[0042] By using borosilicate hollow glass microspheres to reduce the dielectric loss of the resin glue, the low density and low dielectric of the composite material can be further achieved. Preferably, the density of the borosilicate hollow glass microspheres is 0.3-0.5 g / cm 3 , particle size D50 is 40-60μm, and particle size D90 is 60-90μm.
[0043] The present invention adds borosilicate hollow glass microspheres to a specially formulated epoxy resin composition with lower polarity, so that the prepared composite material has the characteristics of low density, low dielectric, high strength and low dielectric loss. The dielectric loss at 5GHz can be lower than 0.01, so it has higher high-frequency signal transmittance. In addition, by adding a low-polarity toughening agent, the bending toughness of the composite material is improved without affecting the flatness, which is more suitable for the demand for consumer electronic product casings and peripheral products in the 5G communication era.
[0044] Specifically, the low polarity curing agent includes one or more of active ester, styrene maleic anhydride resin, benzoxazine resin and bismaleimide resin. These low polarity curing agents are selected to reduce the dielectric loss of the composite material to below 0.01.
[0045] The dielectric loss of epoxy resin composites cured by traditional curing agents such as dicyandiamide and phenolic resin is basically above 0.012. The reaction mechanism of using amines and active esters to cure epoxy resin is compared. Figure 2As shown, the curing reaction using these traditional curing agents is accompanied by the ring-opening reaction of the epoxy group to generate secondary alcohol hydroxyl groups, resulting in a large amount of polar hydroxyl groups in the cured product. However, there is no secondary alcohol hydroxyl group in the cured product after the active ester reacts with the epoxy resin, so it has lower dielectric loss and water absorption. Styrene is a non-polar group in the styrene-maleic anhydride copolymer, which has extremely low dielectric loss. Maleic anhydride, as a curing agent for epoxy resin, can avoid the generation of polar hydroxyl groups in the curing reaction process, increase the ratio of styrene groups in the copolymer, and further reduce dielectric loss.
[0046] If it is necessary to further reduce the dielectric loss of the composite material to less than 0.008, then select the lower polar special resins such as benzoxazine resin and bismaleimide resin. Benzoxazine has good molecular structure design, and by introducing dicyclopentadiene, the dielectric constant of benzoxazine resin can be reduced to 2.8, and the dielectric loss can reach 0.005, and the dicyclopentadiene group also improves the brittleness of benzoxazine at the same time. Cyanate resin can also be selected, and its types are many, and different structures have different performances, but they are the triazine ring structure with high symmetry generated after curing polymerization, which is mainly a reticular polymer, and can have a stable dielectric constant of 2.7-3.0 and a dielectric loss less than 0.007 in a wide frequency range of 1MHz-10GHz.
[0047] Specifically, the mass fractions of each component in the resin glue are: 80-120 parts of modified epoxy resin; 5-50 parts of low polarity toughening agent; 20-100 parts of low polarity curing agent; 0.5-1.5 parts of accelerator; 20-80 parts of borosilicate hollow glass microspheres. In practical applications, and in actual production, each component of the resin glue (except the solvent) is calculated by weight of the non-volatile matter, and by using a solvent, the solid content of the resin glue is controlled to 50-75%. In practical applications, the amount of curing agent used is 20-100 parts, which can take into account the equivalent and dielectric properties of the groups participating in the curing reaction, while improving the overall dielectric properties as much as possible, and avoiding excessive amounts that lead to a decrease in other overall properties, such as mechanical strength, interlayer bonding, etc.
[0048] Specifically, the modified epoxy resin includes one or more of dicyclopentadiene phenol modified epoxy resin, biphenyl type epoxy resin and isocyanate modified epoxy resin. Basic epoxy resins such as bisphenol A type epoxy resins can also be used. Using low polar epoxy resins can achieve lower dielectric constants and dielectric losses.
[0049] Specifically, the accelerator includes one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, N,N-dimethylaminopyridine, 2,4,6-tris(dimethylaminomethyl)phenol and diisopropylbenzene peroxide, which can reduce the temperature of the curing reaction and accelerate the curing reaction speed.
[0050] Specifically, the solvent includes one or more of acetone, butanone, xylene, ethylene glycol monomethyl ether and cyclohexanone, which dissolves and disperses other components and adjusts the viscosity to a suitable range to facilitate gluing.
[0051] Specifically, according to the method for preparing a lightweight, high-toughness, high-frequency, wave-transparent composite material according to claim 1, it is characterized in that: S1 also includes adding an auxiliary agent, and the auxiliary agent includes one or more of a pigment, a cross-linking auxiliary agent, an antioxidant and an ultraviolet absorber.
[0052] In actual production, the addition point of the additives is: after the modified epoxy resin, low-polarity toughening agent, low-polarity curing agent and accelerator are added to the solvent to form a homogeneous solution; the pigment can be a powder, including one or more of titanium dioxide, carbon black, solvent black and aniline black; it can also be a completely ground color paste; the cross-linking additive can be triallyl isocyanurate TAIC.
[0053] Specifically, the baking temperature in S2 is 100-180° C., and the baking time is 2-10 min; preferably, the baking temperature is 120-150° C., and the baking time is 3-6 min. The resin fluidity of the prepreg is adjusted by controlling the baking time.
[0054] Specifically, the glass fiber cloth is electronic grade glass fiber cloth, and the basis weight of the electronic grade glass fiber cloth is 48-105g / m 2 , according to actual needs, choose electronic grade glass fiber cloth with different basis weights, such as basis weight of 48g / m 2 1080 glass fiber cloth, basis weight is 78g / m 2 2113 glass fiber cloth, basis weight is 105g / m 2 2116 fiberglass cloth, etc.
[0055] A light-weight, high-toughness, high-frequency, wave-transmitting composite material is prepared by the preparation method of the light-weight, high-toughness, high-frequency, wave-transmitting composite material.
[0056] Example 1
[0057] This embodiment provides a lightweight, high-toughness, high-frequency, wave-transmitting composite material, and the specific preparation steps are as follows:
[0058] S1, add 100 parts of phenol biphenyl epoxy resin with epoxy equivalent weight of 275g / eq, 35 parts of epoxidized polybutadiene, 85 parts of active ester resin, 1.1 parts of N,N-dimethylaminopyridine to 175 parts of butanone, stir and disperse evenly, then add 50 parts of 0.38g / cm 3 Add the borosilicate hollow glass microspheres into the mixed solution and stir evenly to obtain a resin glue solution;
[0059] S2, the basis weight is 105g / m 2The 2116 glass fiber cloth was immersed in the resin glue, taken out after being completely soaked, and then placed in a 160°C oven for baking for 4.5 minutes to obtain a prepreg, the resin content RC value of which was 43.5%, and the resin fluidity RF was 10%;
[0060] S3, stack 4 prepregs cut at zero degree and of the same specification, place them in a mold covered with a release film for molding, the molding temperature is 175℃, the molding pressure is from 5kg / cm 2 Stepwise pressurization up to 15kg / cm 2 After molding for 10 minutes, the mold is removed and placed in a molding fixture to cool to 25°C to obtain a target product with a 3D structure and an overall thickness of about 0.5 mm.
[0061] Example 2
[0062] This embodiment provides a lightweight, high-toughness, high-frequency, wave-transmitting composite material, and the specific preparation steps are as follows:
[0063] S1. Add 100 parts of phenol biphenyl epoxy resin with an epoxy equivalent of 275 g / eq, 25 parts of terminal hydroxyl polybutadiene, 75 parts of active ester resin, and 0.9 parts of N,N-dimethylaminopyridine to 145 parts of butanone, stir and disperse evenly, and then add 20 parts of a density of 0.46 g / cm 3 Add the borosilicate hollow glass microspheres into the mixed solution and stir evenly to obtain a resin glue solution;
[0064] S2, the basis weight is 105g / m 2 The 2116 glass fiber cloth was immersed in the resin glue, taken out after being completely soaked, and then placed in a 160°C oven for baking for 5 minutes to obtain a prepreg, the resin content RC value of which was 48.5%, and the resin fluidity RF was 15%;
[0065] S3. Stack four prepregs cut at zero degree and of the same specification, place them in a mold covered with a release film for molding, the molding temperature is 175°C, and the molding pressure is from 0.1-0.5kg / cm 2 Stepwise pressurization up to 20kg / cm 2 After molding for 10 minutes, the mold is removed and placed in a molding fixture to cool to 25°C to obtain a target product with a 3D structure and an overall thickness of about 0.5 mm.
[0066] Example 3
[0067] This embodiment provides a lightweight, high-toughness, high-frequency, wave-transmitting composite material, and the specific preparation steps are as follows:
[0068] S1, add 100 parts of phenol biphenyl epoxy resin with epoxy equivalent weight of 275g / eq, 35 parts of maleic anhydride modified butadiene styrene copolymer, 80 parts of active ester resin, 1 part of N,N-dimethylaminopyridine to 190 parts of butanone, stir and disperse evenly, then add 75 parts of density 0.38g / cm 3 Add the borosilicate hollow glass microspheres into the mixed solution and stir evenly to obtain a resin glue solution;
[0069] S2, the basis weight is 78g / m 2 The 2113 glass fiber cloth was immersed in the resin glue, taken out after being completely soaked, and then placed in a 160℃ oven for baking for 3.5 minutes to obtain a semi-cured sheet, whose resin content RC value was 50.5% and resin fluidity RF was 10%;
[0070] S3, stack 4 prepregs cut at zero degree and of the same specification, place them in a mold covered with a release film for molding, the molding temperature is 175℃, the molding pressure is from 5kg / cm 2 Stepwise pressurization up to 10kg / cm 2 After molding for 10 minutes, the mold is removed and placed in a molding fixture to cool to 25°C to obtain a target product with a 3D structure and an overall thickness of about 0.5 mm.
[0071] Example 4
[0072] The prepreg prepared in Example 3 was placed in the middle, and a prepreg prepared in Example 2 was placed on the top and bottom. After the combination was completed, it was placed in a mold covered with a release film for molding. The molding temperature was 170°C and the molding pressure was 5 kg / cm 2 Stepwise pressurization up to 12kg / cm 2 After molding for 10 minutes, the mold is removed and placed in a molding fixture to cool to 25°C to obtain a target product with a 3D structure and an overall thickness of about 0.5 mm.
[0073] Example 5
[0074] This embodiment provides a lightweight, high-toughness, high-frequency, wave-transmitting composite material, and the specific preparation steps are as follows:
[0075] S1, add 100 parts of dicyclopentadiene phenol modified epoxy resin with an epoxy equivalent weight of 300g / eq, 25 parts of maleic anhydride modified butadiene styrene copolymer, 70 parts of styrene maleic anhydride resin, 3 parts of crosslinking aid, 0.1 parts of initiator, 0.7 parts of 2-ethyl-4-methylimidazole to 145 parts of butanone, stir and disperse evenly, then add 25 parts of a density of 0.46g / cm 3 Add the borosilicate hollow glass microspheres into the mixed solution and stir evenly to obtain a resin glue solution;
[0076] S2, the basis weight is 105g / m 2 The 2116 glass fiber cloth was immersed in the resin glue, taken out after being completely soaked, and then placed in a 160°C oven for baking for 3.5 minutes to obtain a prepreg, the resin content RC value of which was 39%, and the resin fluidity RF was 7%;
[0077] S3, stack 4 prepregs cut at zero degree and of the same specification, place them into a mold covered with a release film for molding, the molding temperature is 170℃, the molding pressure is from 5kg / cm 2 Stepwise pressurization up to 20kg / cm 2 After molding for 10 minutes, the mold is removed and placed in a molding fixture to cool to 25°C to obtain a target product with a 3D structure with an overall thickness of about 0.4 mm.
[0078] Example 6
[0079] This embodiment provides a lightweight, high-toughness, high-frequency, wave-transmitting composite material, and the specific preparation steps are as follows:
[0080] S1, add 100 parts of isocyanate modified epoxy resin with epoxy equivalent weight of 300g / eq, 30 parts of maleic anhydride modified butadiene styrene copolymer, 35 parts of styrene maleic anhydride resin, 10 parts of modified bismaleimide resin, 15 parts of modified benzoxazine resin, 5 parts of crosslinking aid, 0.1 parts of initiator, 0.9 parts of 2-ethyl-4-methylimidazole to 180 parts of butanone, stir and disperse evenly, then add 75 parts of density 0.38g / cm 3 Add the borosilicate hollow glass microspheres into the mixed solution and stir evenly to obtain a resin glue solution;
[0081] S2, the basis weight is 105g / m 2 The 2116 glass fiber cloth was immersed in the resin glue, taken out after being completely soaked, and then placed in a 160°C oven for baking for 4 minutes to obtain a prepreg, the resin content RC value of which was 50.5%, and the resin fluidity RF was 15%;
[0082] S3, stack 4 prepregs cut at zero degree and of the same specification, place them in a mold covered with a release film for molding, the molding temperature is 180℃, the molding pressure is from 5kg / cm 2 Stepwise pressurization up to 10kg / cm 2 After molding for 10 minutes, the mold is removed and placed in a molding fixture to cool to 25°C to obtain a target product with a 3D structure and an overall thickness of about 1.0 mm.
[0083] Comparative Example 1
[0084] This comparative example provides a composite material, and the specific preparation steps are as follows:
[0085] S1, adding 80 parts of bisphenol A epoxy resin with an epoxy equivalent weight of 450 g / eq and 20 parts of bisphenol A epoxy resin with an epoxy equivalent weight of 185 g / eq to 35 parts of acetone, stirring and dispersing them uniformly to obtain a first solution;
[0086] Add 3 parts of dicyandiamide and 0.25 parts of 2-methylimidazole to 35 parts of ethylene glycol monomethyl ether, dissolve and disperse them uniformly, and obtain a second solution;
[0087] Add the second solution to the first solution and stir evenly. Then add 24 parts of a density of 0.38 g / cm 3 High-performance borosilicate hollow glass microspheres are added into the mixed solution and stirred evenly to obtain a resin glue solution;
[0088] S2, the basis weight is 105g / m 2 The 2116 glass fiber cloth was immersed in the resin glue, taken out after being completely soaked, and then placed in a 150°C oven for baking for 4 minutes to obtain a prepreg, the resin content RC value of which was 43.5%, and the resin fluidity RF was 10%;
[0089] S3, stack 4 prepregs cut at zero degree and of the same specification, place them into a mold covered with a release film for molding, the molding temperature is 160℃, the molding pressure is from 5kg / cm 2 Stepwise pressurization up to 15kg / cm 2 After molding for 10 minutes, the mold is removed and placed in a molding fixture to cool to 25°C to obtain a target product with a 3D structure and an overall thickness of about 0.5 mm.
[0090] Comparative Example 2
[0091] This embodiment provides a lightweight, high-toughness, high-frequency, wave-transmitting composite material, and the specific preparation steps are as follows:
[0092] S1, add 100 parts of phenol biphenyl epoxy resin with epoxy equivalent weight of 275g / eq, 35 parts of epoxidized polybutadiene, 85 parts of active ester resin, 0.2 parts of N,N-dimethylaminopyridine to 175 parts of butanone, stir and disperse evenly, then add 50 parts of 0.38g / cm 3 Add the borosilicate hollow glass microspheres into the mixed solution and stir evenly to obtain a resin glue solution;
[0093] S2, the basis weight is 105g / m 2 The 2116 glass fiber cloth was immersed in the resin glue, taken out after being completely soaked, and then placed in a 160°C oven for baking for 4.5 minutes to obtain a prepreg, the resin content RC value of which was 43.5%, and the resin fluidity RF was 10%;
[0094] S3, stack 4 prepregs cut at zero degree and of the same specification, place them in a mold covered with a release film for molding, the molding temperature is 175℃, the molding pressure is from 5kg / cm 2 Stepwise pressurization up to 15kg / cm 2 After molding for 10 minutes, the mold is removed and placed in a molding fixture to cool to 25°C to obtain a target product with a 3D structure and an overall thickness of about 0.5 mm.
[0095] Comparative Example 3
[0096] This embodiment provides a lightweight, high-toughness, high-frequency, wave-transmitting composite material, and the specific preparation steps are as follows:
[0097] S1. Add 100 parts of phenol biphenyl epoxy resin with an epoxy equivalent of 275 g / eq, 85 parts of active ester resin, and 1.1 parts of N,N-dimethylaminopyridine to 130 parts of butanone, stir and disperse evenly, and then add 45 parts of a density of 0.38 g / cm 3 Add the borosilicate hollow glass microspheres into the mixed solution and stir evenly to obtain a resin glue solution;
[0098] S2, the basis weight is 105g / m 2 The 2116 glass fiber cloth was immersed in the resin glue, taken out after being completely soaked, and then placed in a 160°C oven for baking for 4.5 minutes to obtain a prepreg, the resin content RC value of which was 43.5%, and the resin fluidity RF was 10%;
[0099] S3, stack 4 prepregs cut at zero degree and of the same specification, place them in a mold covered with a release film for molding, the molding temperature is 175℃, the molding pressure is from 5kg / cm 2 Stepwise pressurization up to 15kg / cm 2 After molding for 10 minutes, the mold is removed and placed in a molding fixture to cool to 25°C to obtain a target product with a 3D structure and an overall thickness of about 0.5 mm.
[0100] Comparative Example 4
[0101] S1. Add 100 parts of phenol biphenyl epoxy resin with an epoxy equivalent of 275 g / eq, 85 parts of active ester resin, and 1.1 parts of N,N-dimethylaminopyridine to 130 parts of butanone, stir and disperse evenly, and then add 45 parts of a density of 0.38 g / cm 3 Add the borosilicate hollow glass microspheres into the mixed solution and stir evenly to obtain a resin glue solution;
[0102] S2, the basis weight is 105g / m 2The 2116 glass fiber cloth was immersed in the resin glue, taken out after being completely soaked, and then placed in a 160°C oven for baking for 4.5 minutes to obtain a prepreg, the resin content RC value of which was 43.5%, and the resin fluidity RF was 10%;
[0103] S3, stack 4 prepregs cut at 45 degrees and of the same specifications, place them in a mold covered with a release film for molding, the molding temperature is 160℃, and the molding pressure is 5kg / cm 2 Stepwise pressurization up to 25kg / cm 2 After molding for 10 minutes, the mold is removed and placed in a molding fixture to cool to 25°C to obtain the target product.
[0104] If the materials mentioned in the above embodiments and comparative examples are in liquid form, they need to be stirred and dispersed evenly; if they are solid, they need to be stirred until they are completely dissolved to avoid affecting the preparation of the target product due to insufficient dissolution.
[0105] The materials used in the above embodiments and comparative examples are as follows:
[0106] Toughening agent: The epoxy polybutadiene is the JP-100 model produced by Japan Soda, the manufacturer of the maleic anhydride modified butadiene-styrene copolymer is Crayville (Guangzhou) Chemical Co., Ltd., the model is Ricon184MA6, and the terminal hydroxyl polybutadiene is the HTPB-3700 model produced by Tianyuan New Materials.
[0107] Curing agent: The manufacturer of active ester is LTY19015 of Tongyu New Materials (Guangdong) Co., Ltd. or DFE617L of Sichuan Dongcai Technology Group Co., Ltd., and the styrene maleic anhydride resin is EF-30 produced by Crayville (Guangzhou) Chemical Co., Ltd. or TMH8003 produced by Tongyu New Materials (Guangdong) Co., Ltd. The manufacturer of modified benzoxazine resin and modified bismaleimide resin is Tongyu New Materials (Guangdong) Co., Ltd., the model of modified benzoxazine resin is TBN8730K70, and the model of modified bismaleimide resin is TBM7200.
[0108] Modified epoxy resin: The manufacturer of dicyclopentadiene modified epoxy resin is Chengdu Keyi Polymer Technology Co., Ltd., model CE1000; the manufacturer of biphenyl type epoxy resin is Shandong Shengquan Chemical Co., Ltd., model SQXN-323; the manufacturer of isocyanate modified epoxy resin is Tongyu New Materials (Guangdong) Co., Ltd., model TER296K75.
[0109] Accelerator: 2-ethyl-4-methylimidazole is 2E4Mz from Siguo Chemical.
[0110] Hollow glass microspheres: H38 or H46 from Zhongke Yali.
[0111] Relevant performance tests were performed on the above embodiments and comparative examples.
[0112] Among them, the testing method of bending toughness is as follows:
[0113] (1) Process the target product into the desired shape through CNC;
[0114] (2) Select the test position (depending on the characteristics of the target product) and the bending angle. For each target product, three test positions should be evenly selected along the length direction, and the target product should be pressed and fixed on the automatic bending equipment;
[0115] (3) Perform a bending test according to the bending angles required by the drawings. If there are no bending angle requirements on the drawings, the following standards shall be followed: the bending angles of the large surface of the battery cover are 30° and 60°, and the bending angle of the camera hole is 30°;
[0116] (4) Use automatic bending equipment, the distance from the support rod to the right pressure rod is 3mm, the bending speed is 9° per second (the actual gear is adjusted according to the bending speed), each target product must cover the camera hole position test, and both the front and back sides must be tested;
[0117] (5) After the test is completed, remove the target product and use adhesion test tape to stick and pull it 3 times to check the damage of the surface coating.
[0118] Note: The bending test is closely related to the appearance of the back cover of the electronic product. The bending test needs to be done with the back cover of the electronic product with the same shape and structure to be comparable, so as to compare the difference in bending toughness of the target products prepared with different resin formulas and processes. Generally speaking, the larger the 3D curvature, the higher the requirement for bending toughness.
[0119] The test requirements for bending toughness are as follows:
[0120] Battery cover: No cracks on the surface after bending 30°, no breakage, paint or ink breakage after bending 60°. Camera hole position: No breakage, coating or ink fall-off after bending 20°.
[0121] The relevant performance test results of each embodiment and comparative example are shown in Table 1:
[0122]
[0123]
[0124] Table 1
[0125] Table 1 records the density, bending strength, dielectric constant at 5 GHz, dielectric loss, bending toughness and flatness of all the above embodiments and comparative examples.
[0126] Example 1, Example 2, Example 3 and Example 4 all use a low polarity curing agent, a low polarity toughening agent and borosilicate hollow glass microspheres, and the dielectric loss at 5 GHz is lower than 0.01. While having good flatness, it also has excellent bending toughness. Among them, Example 3 reduces the amount of boric acid silicate hollow glass microspheres added, resulting in a higher dielectric constant and dielectric loss than Example 1 and Example 2. Compared with the examples, Comparative Examples 1 and Comparative Examples 2 have a dielectric loss at 5 GHz higher than 0.01, and do not have bending toughness. Comparative Example 2 reduces the amount of accelerator added, resulting in a longer time and a higher temperature for curing. Insufficient curing will result in stratification, and there are residual unreacted polar groups, resulting in increased dielectric loss. Comparative Example 3 does not add a low-polarity toughening resin, so although its dielectric loss at 5 GHz is lower than 0.01 and has good flatness, it does not have bending toughness. The cutting angle of Comparative Example 4 is 45 degrees, so although its dielectric loss at 5 GHz is lower than 0.01 and has bending toughness, it does not have good flatness.
[0127] The present invention enables the prepared composite material to have the characteristics of low density, low dielectric constant, high strength and low dielectric loss, and improves its bending toughness without affecting the flatness of the composite material. It can be applied to electronic products with 3D structures and is suitable for the demand for consumer electronic product casings and their peripheral products in the 5G communication era.
[0128] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material, characterized in that: The following steps are involved: S1. Add modified epoxy resin, low polar toughening agent, low polar curing agent and accelerator to the solvent, stir to dissolve evenly, then add borosilicate hollow glass microspheres, stir to disperse evenly, and obtain resin glue; S2, immersing the glass fiber cloth into the resin glue solution, taking it out after it is completely soaked, and baking it to obtain a prepreg; S3, stacking a plurality of the prepregs, placing them in a mold, and heating them at 120-200°C and 5-25kg / cm 2 The mold is pressed for 5-30 minutes under the conditions of , and then demoulding and placing in a shaping fixture for cooling to obtain the target product; The low polar toughening agent includes one or more of epoxidized polybutadiene, maleic anhydride modified butadiene-styrene copolymer and terminal hydroxyl polybutadiene, and the density of the borosilicate hollow glass microspheres is 0.2-0.6 g / cm 3 , particle size D50 is 30-75μm, and particle size D90 is 60-120μm.
2. The method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material according to claim 1, characterized in that: The low polarity curing agent includes one or more of active ester, styrene maleic anhydride resin, benzoxazine resin and bismaleimide resin.
3. The method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material according to claim 1, characterized in that: The mass fractions of each component in the resin glue are: 80-120 parts of modified epoxy resin; 5-50 parts of low polarity toughening agent; 20-100 parts of low polarity curing agent; Accelerator 0.5-1.5 parts; 20-80 parts of borosilicate hollow glass microspheres.
4. The method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material according to claim 1, characterized in that: The modified epoxy resin includes one or more of dicyclopentadiene phenol modified epoxy resin, biphenyl type epoxy resin and isocyanate modified epoxy resin.
5. The method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material according to claim 1, characterized in that: The accelerator includes one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, N,N-dimethylaminopyridine, 2,4,6-tris(dimethylaminomethyl)phenol and diisopropylbenzene peroxide.
6. The method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material according to claim 1, characterized in that: The solvent includes one or more of acetone, butanone, xylene, ethylene glycol monomethyl ether and cyclohexanone.
7. The method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material according to claim 1, characterized in that: The method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material according to claim 1 is characterized in that: in S1, an auxiliary agent is also added, and the auxiliary agent includes one or more of a pigment, a cross-linking auxiliary agent, an antioxidant and a UV absorber.
8. The method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material according to claim 1, characterized in that: The baking temperature in S2 is 100-180° C., and the baking time is 2-10 minutes.
9. The method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material according to claim 1, characterized in that: The glass fiber cloth is electronic grade glass fiber cloth, and the basis weight of the electronic grade glass fiber cloth is 48-105g / m 2 .
10. A lightweight, high-toughness, high-frequency, wave-transmitting composite material, characterized in that: The composite material is prepared according to the method for preparing a lightweight, high-toughness, high-frequency, wave-transmitting composite material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lightweight 3D rear cover plate for mobile phone and processing technology of lightweight 3D rear cover plate
CN114801244A
High temperature-resistant epoxy resin composition for pultrusion and preparation method
CN103881301A
Thermosetting resin composition and prepreg, laminated board and metal-clad laminate using same
CN109608828A
Polyphenyl ether resin composition and application thereof
CN109749396A
Epoxy resin composition, adhesive film and light sealing material
CN118496792A